GPs' views and experiences of managing patients with personality disorder: a qualitative interview study. Issue 2 (27th February 2019) - French, Lydia; Moran, Paul; Wiles, Nicola; Kessler, David; Turner, Katrina M
Abstract : Objective: The aim of this study was to explore GPs' views and experiences of managing patients with personality disorder (PD), and their views on the role of the Improving Access to Psychological Therapies (IAPT) programme as a support service. Design: In-depth interviews, analysed thematically. Participants: Fifteen GPs (7 women and 8 men) of varying age and clinical experience, working in practices that differed in terms of the socio-demographic characteristics of their patient populations. Setting: Twelve general practices based in the West of England, UK. Results: GPs described patients with PD as being challenging to work with and that this work required dedicated time and care. They described experiencing particular difficulty with monitoring their patient's mental health, as well as having little knowledge about the efficacy or availability of treatments for their attenders with PD. They were aware that this patient population often experienced poor mental health and reported a propensity for them to fall into the gap between primary and secondary mental health services, leaving GPs with little choice but to improvise their own management plans, which occasionally involved funding third-sector treatment options. In terms of IAPT services' role in managing these patients, GPs wanted shorter waiting times, better inter-agency communication, more highly trained therapists and more treatment options for patients with PD. They also wanted the service to be able to 'hold' patients with PD in treatment over a longer period than currently offered. Conclusions: Findings suggest that, overall, GPs did not consider National Health Service mental health services to offer an effective treatment for patients with PD. While they considered the IAPT programme to be a valuable service for patients with less complex mental health needs, such as depression and anxiety; they felt that the current service provision struggled to meet the needs of patients with more complex mental health needs, as exemplified by people with PD.